ANALISIS KEKUATAN PATAH DAN DAYA SERAP AIR PAPAN KOMBINASI SERAT DENGAN LAMINASI BAMBU BETUNG (Dendrocalamus asper) - Raizal Fahmi Solihat; Yogi Saputra (Fakultas Kehutanan Universitas Winaya Mukti, 2019)
The problem faced by the wood processing industry in Indonesia today is the shortage of wood raw materials. This occurs because the speed at which timber is used is not balance with the speed at which new stands are build. Meanwhile, the need for wood for furniture, building materials and other needs continues to increase in line with population growth. Therefore, it is necessary to find alternative raw materials for the wood processing industry. Bamboo is one material that can be use for this purpose. Bamboo is a long fiber and has advantages in terms of the harvest period, namely within 3-4 years it can be harvested, shorter than 8-20 years for fast-growing timber species. In this research, a combination of fiber and laminate boards with epoxy adhesive. The material used is the type of betung bamboo (Dendrocalamus asper) and then tested on the combination of fiber and laminated bamboo boards there are 3 tests, namely fracture strength, absorption capacity and density. The results of this research indicate that from the treatment of 255g adhesive and 127.5g of fiber has a higher average compared to 127.5g of adhesive and 255g of fiber. From the test results, the combination of fiberboards and laminate boards as HDF (Hard Dencity Fiberboard) classified which can be used for materials for making adhesive walls, ceilings, pinyi and containers. However, in contrast to the 127.5g adhesive and 255g fiber treatment included in the MDF (Medium Dencity fiberboard) classification, furniture such as household appliances, molding, window frames, door skins and car dashboards are used.